Effects of irrigation and weed-control methods on growth of weed and rice - Towa, Jacob Jeremiah; Xiangping, Guo (International Journal of Agricultural and Biological Engineering, 2014)
A field experiment was conducted to study the effects of weeds control methods and an irrigation model on rice growth as well as water consumption and weed quantity in the paddy field. In conventional paddy rice production, one of the most important irrigated crops, a significant amount of irrigation water is lost due to percolation and evaporation. A new irrigation model called the Rain-Catching and Controlled Irrigation (RCCI) model has been developed as a viable water-saving technology in the production of paddy rice. In this study the performance of the RCCI model has been analyzed under mulching, hand weeding and weedy conditions in Jiangsu Province of China. The experiment was laid out in Randomized Complete Block Design (RCBD) with three replications and nine treatments. The three replicates consisted of three water management regimes: high dry high flooding (HD-HF), high dry low flooding (HD-LF), and shallow and frequent irrigation (SF) water treatment. The RCCI model was adopted in HD-HF and HD-LF while Flooding Irrigation (CFI) was adopted in SF as a control. The nine treatments were equally divided under mulching, hand weeding and weedy conditions. The lowest and maximum irrigation water delivery was 244.86 mm in mulching and 429.22 mm in hand weeding, respectively at HD-HF. And the lowest and maximum irrigation water delivery was 300.1 mm in the mulching field and 680.72 mm under hand weeding, respectively at HD-LF. The Nanjing 44 rice variety was used. It was observed that weed density and dry weight were significantly influenced by the amount of irrigation water in all the mulching, hand weeding and weedy plots. Considering yield and the number of irrigations, the RCCI model produced better results than CFI. Mulching under RCCI was an effective method to control weeds and reduce labor cost. In addition, mulching decreases the use of herbicides and the risk of pollution. On the other hand, mulching could improve yield and save water. Keywords: irrigation, weed control, mulching, hand weeding, RCCI, weed population, agronomy traits, paddy rice DOI: 10.3965/j.ijabe.20140705.003 Citation: Towa J J, Guo X P. Effects of irrigation and weed-control methods on growth of weed and rice. Int J Agric & Biol Eng, 2014; 7(5): 22－33.